Influencia del funcionamiento familiar en el desarrollo de la inteligencia emocional en los estudiantes universitarios de la provincia de Chimborazo. - Paredes Paredes, Esteban Patricio (2024)
The current research describes the influence of family functioning on university students' emotional intelligence development in the province of Chimborazo. The research uses a quantitative approach, non-experimental design, descriptive, cross-sectional, and field approach. The level of research is correlational. The population consisted of 278 students in the Psychopedagogy career program at Universidad Nacional De Chimborazo. The researcher intentionally selected the population using inclusion and exclusion criteria with 100 participants, of which 63% are women and 37% are men, with an average age of 21.75 and a predominance of 88% of mestizo ethnic self-identification. The family functioning perception test (FF-SIL) and the Trait Meta-Mood Scale TMMS-24 were applied. The analysis of results around family functioning revealed that perception prevails in a moderately functional range. Regarding emotional intelligence, it was possible to find that the attention component preponderates with 51% adequate attention; in the clarity component ad, understanding predominates with 52%, and in repair, adequate regulation prevails with 57%. It was possible to identify a positive correlation p 0.00 between family functionality and each component of emotional intelligence. In conclusion, it is a fact that, at a higher level of family functioning, the development of emotional intelligence is favored.